2004
DOI: 10.1109/tmi.2003.819934
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Use of Vibro-Acoustography forBrachytherapy Metal Seed Imaging:A Feasibility Study

Abstract: Vibro-acoustography method is explored for detecting and imaging brachytherapy metal seeds in gel phantoms. In a previous paper, we have shown that some immersed objects' resonance frequencies could be detected by vibro-acoustography. Here, we use this idea to optimize the vibro-acoustic excitation of two different sized brass seeds implanted in an agar gel phantom. In the experiments, the best excitation vibration frequencies were determined either by calculating fundamental resonance frequencies for each of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(45 citation statements)
references
References 19 publications
1
44
0
Order By: Relevance
“…In the medical field, VA has been successfully used for imaging small particles such as calcium deposits on heart valve leaflets [15], microcalcifications in breast tissue [16][17][18][19], calcifications in arteries [11,20], excised human cancerous liver tissue [21], and standard brachytherapy seeds in gel phantoms [22].…”
Section: Introductionmentioning
confidence: 99%
“…In the medical field, VA has been successfully used for imaging small particles such as calcium deposits on heart valve leaflets [15], microcalcifications in breast tissue [16][17][18][19], calcifications in arteries [11,20], excised human cancerous liver tissue [21], and standard brachytherapy seeds in gel phantoms [22].…”
Section: Introductionmentioning
confidence: 99%
“…Each pixel on the observation plane corresponds to the contribution (sum) of the acoustic response of all elements on the source plane. The acoustic responses for frequencies f 1 and f 2 are given by (10) where A mn is an apodization term to define the different apertures for ω 1 and ω 2 which represents the assignment of channel considering time delay and frequency of excitation (k = 1,2), and p mn is the contribution of pressure of each element in the source plane at mncoordinate. A mn is 1 when an element is assigned ω and 0 otherwise.…”
Section: Numeric Implementation For the Acoustic Field Analysismentioning
confidence: 99%
“…These problems can be partially solved by using a water tank to host the transducer. Multiple laboratory VA studies using the confocal transducer in a water tank have been performed in breast [7] [8], thyroid [9], and prostrate tissues [10] [11] [12] [13]. The same confocal transducer has been also used for in vivo measurements in human breast [14] [15] [16].…”
Section: Introductionmentioning
confidence: 99%
“…TRUS provides sufficient soft tissue contrast to delineate the prostate boundaries. However, despite significant efforts in seed localization from ultrasound, [12][13][14][15][16][17][18] robust seed segmentation in ultrasound is not yet possible. It was shown that up to 25% of the seeds can be missed even through manual segmentation of B-mode images.…”
Section: Introductionmentioning
confidence: 99%